A Pilot Study of the Learning Curve Effect on Technological Safeguards Used in Online Courses - Stevens, Robert; Silver, Lawrence; Campbell, Kitty; Richards, Rhonda (American Journal of Management, 2020)
The March 2020 COVID-19 pandemic caused many universities to move face-to-face and hybrid courses to completely online formats, resulting in increased challenges for using online safeguards to thwart cheating. Although academic misconduct and academic dishonesty among students is nothing new, the literature is inconclusive as to whether there is more cheating in online classes than in face-to-face classes. However, online education has made it much more difficult for instructors to detect instances of cheating even with more technological safeguards. The purpose of this study is to identify faculty use of safeguards in online courses and determine if more experienced online faculty use more safeguards and more technologically oriented safeguards. An Internet survey link was sent to all faculty at a southwestern university.